Muncie, India(na) : Middletown and Asian America - Gupta-Carlson, Himanee (Book collections on Project MUSE., 2018)
This work is a study of South Asian Americans in Muncie, Indiana - the author's hometown. Muncie is the small Midwestern city made famous for being 'typical America' through the Middletown studies.